2020
DOI: 10.3389/fphar.2020.00964
|View full text |Cite
|
Sign up to set email alerts
|

Serious Adverse Drug Reactions and Safety Signals in Children: A Nationwide Database Study

Abstract: Children are more exposed to inappropriate medicine use and its consequent harms. Spontaneous reporting of suspected Serious Adverse Drug Reactions (SADR) increases knowledge and prevention of pharmacotherapy risk. Disproportionality measures are useful to quantify unexpected safety issues associated with a given drug-event pair (signals of disproportionality). This cross-sectional study aimed to assess SADR reporting and safety signals for Brazilian children from 0-12 years old, notified between January 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Due to the lack of consideration for the overall ADR incidence rate in the general population, the result only inflected the status of pediatric cancer patients who have been suffered from ADR in the region, or even more limited. Similar findings were observed in other studies ( 22 , 25 ). Some reasons might have contributed to the high reporting rates in young children.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the lack of consideration for the overall ADR incidence rate in the general population, the result only inflected the status of pediatric cancer patients who have been suffered from ADR in the region, or even more limited. Similar findings were observed in other studies ( 22 , 25 ). Some reasons might have contributed to the high reporting rates in young children.…”
Section: Discussionsupporting
confidence: 93%
“…Data mining in pharmacovigilance databases may guide 1) additional analytical studies in specific populations that may be more susceptible to ADE occurrence and 2) epidemiologic studies for risk quantification and risk-minimization activities ( Emanuel Raschi, 2016 ). Previous studies from our group found relevant signals of disproportionate reporting in pediatric and oncologic care from the former Brazilian database (Notivisa) ( Barcelos et al, 2019 ; Vieira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 79%
“…Systems for active surveillance and projects for detecting signals and monitoring recently approved medications ( Racoosin et al, 2012 ) have been established in other countries. Recent studies involving disproportionality analysis for safety signal screening in children ( Vieira et al, 2020 ) and breast cancer patients ( Barcelos et al, 2019 ) using Notivisa were conducted, demonstrating the potential of this data source. However, Brazil lags behind in terms of research initiatives and decision-making using automated administrative data.…”
Section: Discussionmentioning
confidence: 99%